Molecular autopsy: using the discovery of a novel de novo pathogenic variant in the KCNH2 gene to inform healthcare of surviving family. Issue 12 (December 2018) - Dong, Jingyun; Williams, Nori; Cerrone, Marina; Borck, Christopher; Wang, Dawei; Zhou, Bo; Eng, Lucy S.; Subbotina, Ekaterina; Um, Sung Yon; Lin, Ying; Ruiter, Kevin; Rojas, Lisa; et al.
Abstract: Background: Molecular testing of the deceased (Molecular Autopsy) is an overlooked area in the United States healthcare system and is not covered by medical insurance, leading to ineffective care for surviving families of thousands of sudden unexpected natural deaths each year. We demonstrated the precision management of surviving family members through the discovery of a novel de novo pathogenic variant in a decedent. Methods: Forensic investigation and molecular autopsy were performed on an 18-year-old female who died suddenly and unexpectedly. Co-segregation family study of the first-degree relatives and functional characterization of the variant were conducted. Findings: We identified a novel nonsense variant, NP_000229.1 :p.Gln1068Ter, in the long QT syndrome type II gene KCNH2 in the decedent. This finding correlated with her ante-mortem electrocardiograms. Patch clamp functional studies using transfected COS-7 cells show that hERG-ΔQ1068 has a mixed phenotype, with both gain- (negative voltage shift of steady-state activation curve, the positive shift of the steady-state inactivation curve, and accelerated activation) and loss-of function (reduced current density, reduced surface expression and accelerated deactivation) hallmarks. Loss of cumulative activation during rapid pacing demonstrates that the loss-of-function phenotype predominates. The wild-type channel did not rescue the hERG-ΔQ1068 defects, demonstrating haploinsufficiency of the heterozygous state. Targeted variant testing in the family showed that the variant in KCNH2 arose de novo, which eliminated the need for exhaustive genome testing and annual cardiac follow-up for the parents and four siblings. Interpretation: Molecular testing enables accurate determination of natural causes of death and precision care of the surviving family members in a time and cost-saving manner. We advocate for molecular autopsy being included under the healthcare coverage in US.